Effectiveness of Neuromuscular Electrical Stimulation on Post-Stroke Dysphagia: A Systematic Review of Randomized Controlled Trials - Alamer, Abayneh; Melese, Haimanot; Nigussie, Fetene (Clinical interventions in aging, 2020)
The purpose of this review was to summarize the latest best scientific evidence on the efficacy of neuromuscular electrical stimulation on swallowing function in dysphagic stroke patients. A comprehensive systematic search of literature published between November 2014 and May 2020 was performed using the following electronic databases: PubMed/Medline, CINAHL, PEDro, Science Direct, Google Scholar, EMBASE, and Scopus. Only randomized controlled trials (RCT) evaluating the effect of neuromuscular electrical stimulation on swallowing function in dysphagic stroke patients were included. Physiotherapy Evidence Database (PEDro) has been used to evaluate the risk of bias of included trials. This review was reported in accordance with PRISMA statement guideline. The methodological quality of the studies was determined using PEDro scale and GRADE approach. Evidence of overall quality was graded from moderate to high. Eleven RCTs involving 784 patients were analyzed. The primary outcome measures of this review were functional dysphagia scale (FDS) and standard swallowing assessment. This review found neuromuscular electrical stimulation (NMES) coupled with traditional swallowing therapy could be an optional intervention to improve swallowing function after stroke in rehabilitation department.